Penciptaan Tari "Ngies" pada Prosesi Adat Buang Jong Suku Sawang dengan Pijakan Gerak Tari Kedidi Menggunakan Metode Moving from Within Alma M. Hawkins. - Ida Bagus Ketut Sudiasa; Bambang Kristiono Soewardjo; bujang, Robi Maulana (Jurnal Pendidikan Tari, 2022)
The Creation of Ngies Dance in the Buang Jong Traditional Procession of the Sawang Tribe with the Footing of the Kedidi Dance Using the Form Within Alma M Hawkins Method, Thesis (Final Choreograph), Dance Education Study Program, Faculty of Language and Arts, State University of Jakarta.This dance work raises the story of a traditional ritual that exists in one of the villages in Bangka Belitung, precisely in the Kumbung Village of South Bangka Regency, namely the Buang Jong Ritual, where throwing garbage means the boat can be interpreted as throwing jong the same as throwing the boat. The method used in this dance work Alma M Hawkins’s method from her book Moving from Within through the stages of experiencing, expressing, seeing, feeling, imagining, manifesting, forming, and evaluating. This dance work reveals how the ritual of throwing Jong was carried out through a new dance work with the footing of the Kedidi Dance movement. This work is the result of a personal observer packaged in a video with new dance moves and music.